Textural and geochemical investigation of pyrite in Jacobina Basin, Sao Francisco Craton, Brazil: Implications for paleoenvironmental conditions and formation of pre-GOE metaconglomerate-hosted Au-(U) deposits - Teles, Guilherme S.; Chemale Jr, Farid; Avila, Janaina N.; Ireland, Trevor R.; Dias, Airton N. C.; Cruz, Daniele C. F.; Constantino, Carlos J. L. [UNESP] (Elsevier B.V., 2020)
The Jacobina Basin has a well-preserved sedimentary record, including continental and marine deposits, and hosts Au-(U)Py mineralization in metaconglomerate beds similar to the Witwatersrand gold province. Based on petrographic observations, in situ trace-elements, and multiple sulfur isotope analyses (S-32, S-33, S-34, and S-36) on pyrite from alluvial and marine facies, several types of pyrite were recognized. The pyrite grains identified in the alluvial metaconglomerates resemble those found in several pre-GOE gold-bearing metaconglomerates, including detrital and epigenetic varieties. Detrital inclusion-bearing pyrite is enriched in several redox-sensitive trace-metals as well as Au, which indicate an association with carbonaceous shales. On the other hand, the sources of detrital massive pyrite are more variable and include igneous, metamorphic, and hydrothermal sources from the Paleoarchean hinterland of Jacobina Basin. Epigenetic pyrite in metaconglomerates formed during metamorphism by the recrystallization of detrital pyrite with negligible contributions from external hydrothermal fluids to the basin. Diagenetic and epigenetic pyrite are found in marine lithologies. In a metapelite sample, the pyrite grains formed near the sediment-water column interface, with S sourced from the photolytic sulfate (SO42-, D Delta S-33 < 0) dissolved in the water column. A quartzite sample, in turn, has detrital pyrite grains that were likely reworked from continental deposits, as well as pyrite formed by the assimilation of elemental sulfur (S-8, Delta S-33 > 0) that accumulated in sediment pore water during diagenesis. Significantly, the pyrite associated with terrestrial metasediments shows a wide range in delta S-34 values but quite restricted ranges in Delta S-33 and Delta S-36 values, whereas pyrite associated with the marine metasedimentary rocks exhibits limited delta S-34 values but has a wide range in Delta S-33 values and correlated Delta S-36 values close to the Archean array. These data suggest distinct preservation routes for MIF-S from atmospheric SO42- and S-8 in terrestrial and marine environments. Conditions on the terrestrial surface resulted in re-equilibration of distinct S sources, diminishing the amplitude of the Archean atmospheric signal. In contrast, SO42- dissolved in shallow marine settings while S-8 settled to the floor, favoring the preservation of MIF-S isotopic signatures. Such processes may also explain the apparent differences in interpretations of atmospheric conditions derived from uncharacterized pyrites from Archean sources. Our data suggest that the Earth's atmosphere remained anoxic, and terrestrial conditions were such as to allow the syngenetic accumulation of gold, as recently proposed for the Witwatersrand gold deposits. (C) 2020 Elsevier Ltd. All rights reserved.
Keywords: Au-U-pyrite mineralization; Multiple sulfur isotopes; Jacobina Basin; Sao Francisco Craton